The Role of Notaries in Binding Credit Guarantee Objects to Village Credit Institutions - I Made Pria Dharsana (Law Doctoral Community Service Journal, 2022)
The existence of a Notary in terms of making a credit agreement deed in this LPD, is of course very helpful for the indigenous people in Bali as the customer of the LPD to guarantee legal certainty for the guarantee given to the LPD until the credit provided can be repaid by the customer. If there is already a governance arrangement based on customary law that has legal certainty, then all forms of credit transactions in the LPD, including those related to the binding of credit guarantees, should follow the applicable mechanism as long as it does not conflict with applicable law in the territory of the Unitary State of the Republic of Indonesia. For this reason, it is important to create a customary court to accommodate changes in LPD governance if they have been changed in accordance with customary law. Basically, lending by the LPD is given to anyone who has the ability to repay on condition that it is through a credit agreement between the LPD and krama desa pakraman. LPD lending follows generally accepted credit procedures with some adjustments that emphasize its existence as belonging to the village of Pakraman.